+0  
 
0
111
2
avatar+105 

Simplify (1+i)^2016-(1-i)^2016.

 Oct 7, 2018
 #1
avatar
0

(1+i)^2016 =((1+i)^16)^126 =256^126

(1 - i)^2016=((1-i)^16)^126 =256^126

256^126 - 256^126 =0

 Oct 7, 2018
 #2
avatar+96302 
+1

( 1 + i)^2  =  1 + 2i  + i^2  =  1  + 2i  - 1  = 2i

 

(1 - i)^2  =  1 - 2i  + i^2  =  1  - 2i  - 1  =  -2i

 

So

 

( 1 + i)^2016  - (1 - i)^2016  =

 

[ (1 + i)^2 ] ^1008  -  [ (1 - i)^2 ]^1008  =

 

(2i)^1008  - (-2i)^1008  -

 

(2i)^1008  -  (-2)^1008 * (i)^1008  =           [ (-2)^even power  = 2^even power]

 

(2i)^1008  -  (2)^1008 * i^1008  =

 

(2i)^1008  -  (2i)^1008  =

 

0

 

 

cool cool cool

 Oct 8, 2018

37 Online Users

avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.